Influence of mineral fillers on the fire retardant properties of wood‐polypropylene composites. (10th August 2012) - Nikolaeva, Marina; Kärki, Timo
ABSTRACT The effects of mineral fillers on the fire retardancy of wood‐polypropylene composites have been studied. Wood‐polypropylene composites containing mineral fillers have been compounded in a conical twin‐screw extruder. A composite manufactured without any mineral filler addition has been used as a reference. The flame resistance properties of the composite materials have been studied using the cone calorimeter. The results show that the introduction of mineral fillers into the wood‐polypropylene composites has a favourable effect on the fire resistance properties of the composite materials. The reaction‐to‐fire properties have been improved according to the fire classification of construction products based on the Euroclass system. Copyright © 2012 John Wiley & Sons, Ltd.